Thick Crust City: Kuala Lumpur - Ngiom, Lim Teng (MAJ - Malaysia Architectural Journal, 2025)
The Kueh Lapis or, Layered Cake provides the metaphor for the hypothesis of the thick crust city. The hypothesis suggests that the meaningful city is one that is built up from layers of its past. The layers reveal themselves at the present moment, frozen in time. The layers are mainly physical encrustation that the city inherits from the past. Metaphysical layers could be deduced, or speculated from the physical layers, such as the forms of life that once existed for each layer. It is like excavating the layers to find the underlying evidence of the past and their meanings to complete the narrative of the present. Richness of experience, fulfilment of the senses and opportunities for creativity are part of what makes a thick crust city other than the physical make-up of the city. Time is a factor for the make-up of the thick crust city. Highly-planned new cities need time to become a thick crust city as the city needs changes as one layer is built over another and different forms of life need to inhabit the city over time. A thick crust city requires diversity in activities, cultures and people of different tribes, coming together to provide richness in diversity, prompting high-density interactions. The feed-back loops between different people enhances creativity and tolerance, as well as knowledge. Cities of endearment are thick crust cities and the major cities of the world, which are much spoken about are thick crust cities. Kuala Lumpur is such a city and the paper provides the contents that support the suggestion.